Anti-NMDA receptor encephalitis and vaccination: A disproportionality analysis - Martin, Salomé; Azzouz, Brahim; Morel, Aurore; Trenque, Thierry (Frontiers in Pharmacology, 2022)
Anti–N-methyl-D-aspartate receptor (NMDAR) encephalitis is an auto-immune neurological disorder characterized by the presence in the cerebrospinal fluid of antibodies against the GluN1 subunit of NMDA receptors in the brain. The etiology of the disease remains largely unknown. In this study, we aimed to investigate the possible existence of pharmacovigilance signals relating to a link between vaccination and anti-NMDAR encephalitis. We performed a case/non-case study using data from the World Health Organization pharmacovigilance database (VigiBase) up to 31 December 2021. All individual case study reports (ICSRs) linked to a vaccine and coded with the MedDRA Lower Level Term (LLT) “anti-NMDA receptor encephalitis” were analysed. We calculated the Reporting Odds Ratio (ROR) and 95% Confidence Interval (CI) for each type of vaccine. A total of 29,758,737 ICSRs were registered in VigiBase, of which 70 were coded under the selected LLT, and 29/70 (41.4%) involved a vaccine. Of these cases, 53.8% involved children aged younger than 15 years. The average time to onset of anti-NMDAR encephalitis after vaccination was 87.6±196.0 days. Highest RORs were observed for the diphtheria/polio/tetanus/pertussis vaccine (54.72 [95%CI 26.2-114.3]), yellow fever vaccine (50.02 [95%CI 15.7-159]) and human papillomavirus vaccine (32.89 [15.8-68.7]). 13 patients did not recover, or were left with permanent sequelae; nine patients recovered without sequelae or are on the path to recovery; one patient died. In summary, pharmacovigilance signals were observed for anti-NMDAR encephalitis and vaccination. Clinicians need to be aware of this potential risk, and encourage to report any case of anti-NMDAR encephalitis occurring after vaccination.